Numerical simulating of pre-grouting in multi-jointed rock mass in deep coalmine roadway excavated via TBM. (February 2023) - Xue, Xinran; Zhang, Kai; Ma, Bailong; Xiao, Fangyuan; Jiang, Tao
Abstract: Tunnel Boring Machines (TBMs) have been used in many underground coal mines in China in recent years, most of which are open-type. The open-type TBM is unfavorable to advance in complex geological conditions, especially in heavily jointed rock mass. When the TBM advance in multi-jointed soft rock mass, the surrounding rock frequently damages and deforms around the tunneling face uncontrollably, which brings risk for the workers and reduces the advance rate. Pre-grouting the rock mass ahead before excavating is a common measure used to handle the above-mentioned condition. However, it is difficult to evaluate how the slurry diffuses and how it enhances the rock mass. Therefore, it is short of guidance to determine the parameters of the pre-grouting. In the present research, a 3D Ubiquitous-Multiple-Joint (UMJ) model was first proposed to simulate the mechanical behavior of rock mass affected by multiple sets of joints around the excavating face of TBM. Then, a seepage model with an equivalent anisotropic permeability tensor was proposed to simulate the diffusion of slurry in the jointed rock mass for pre-grouting. Following the in-situ action, the numerical model was first excavated using the UMJ model and then grouted according to the equivalent permeability tensor. After that, the grouted rock mass was enhanced by improving the mechanical parameters of joints. The effect of pre-grouting reinforcement could thus be simulated. Using the method, this paper studied the effect of grouting parameters and proposed some suggestions for TBM tunneling in multi-jointed rock mass.